(untitled) (Acta Scientiarum. Biological Sciences, 2008)
The river Plate coastal plain is located in northeastern Buenos Aires province, where geological events such as sea transgressions and regressions in the Holocene have produced a stratigraphic column with marine-estuarine, fluviatile and continental sediments, as well as a variety of landforms and soils. The aim of this paper is to describe these different coastal settings and their influence in the distribution of plant communities.